Sub-cycle directional control of the dissociative ionization of H2 in tailored femtosecond laser fields - Li, H.; Gong, Xiaochun; Lin, Kang; De Vivie-Riedle, Regina; Tong, X. M.; Wu, J.; Kling, Matthias F. (Journal of Physics B: Atomic, Molecular and Optical Physics, 2017)
Being the simplest molecule on the planet, H2, as well as its isotopes, have been the prototype systems for strong-field molecular physics for decades. Photoionization and dissociation of H2 have been extensively investigated. After single ionization, the electron left in the molecular ion and its microscopic localization around the two dissociating nuclei can be effectively manipulated using intense femtosecond laser fields with broken symmetry. In this paper, we review the recent progress made on the sub-cycle directional control of the dissociative ionization of hydrogen molecules by tailoring the waveform of femtosecond laser fields, including few-cycle pulses and 2-color fields polarized along the same direction (one-dimension) or different directions (two-dimension).
CRIS-Team Scopus Importer:2023-04-20
Keywords: electron localization; few-cycle laser pulses; strong-field physics; two-color femtosecond laser pulses